HUBUNGAN AKTIFTAS FISIK DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI INDOENSIA: META-ANALYSIS STUDY - Khotimah, Nurul Khusnul; Gani, Nurul Fadhila; Nurhidayah; Musdalifah; Rasmawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to review using a meta-analysis approach the relationship between physical activity and blood pressure in hypertensive patients in Indonesia to find out how big the effect size correlation is for these two variables. Methods: The research used a meta-analysis research approach guided by PRISMA. There are several process stages based on PRISMA guidelines, including: Identification, Screening, eligibility and included/excluded. The research results taken are the results of research from Indonesia. So the keywords determined by researchers are